CROP YIELD PREDICTION USING MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is very essential in a farmer's existence. Machine learning has the potential torevolutionize agriculture by altering the revenue situation by producing the optimal produce. Thispaper concentrates on forecasting crop yield by using different machine learning methods.Machine learning algorithm predictions will aiding producers in choosing which crop to grow tomaximize output by taking into accountlike the climate, humidity, location, and so forth. Thisarticle discusses forecast of crop output using machine learning Approach and goes into depthabout different approaches for disease detection and Classification.